Rosie Powell Davies - Thesis submitted to the University of Oxford in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology (DClinPsych) - Powell Davies, R (2024)

(untitled)
Paper 1: The relationship between the experience of childhood adversity and mental health outcomes for fathers in the perinatal period: a systematic review